From action planning and plan enactment to fruit consumption: moderated mediation effects - Stefanie Kasten; Liesbeth van Osch; Sander Matthijs Eggers; Hein de Vries (BMC Public Health, 2017)
Abstract Objectives Sufficient fruit consumption is beneficial for a healthy live. While many Dutch adults intent to eat the recommended amount of fruit, only 5–10% of the population actually adheres to the recommendation. One mechanism that can help to narrow this gap between intention and actual fruit consumption is action planning. However, action planning is only assumed to be effective if plans are enacted. This study assessed which action plans are made and enacted, and further aimed to investigate two main hypotheses: 1. the effect of action planning (at T1) on fruit consumption (at T2) is mediated by plan enactment (at T3); 2. positive intentions (2a), high self-efficacy (2b) and a strong habit to eat fruit (2c) enhance the mediation of plan enactment, whereas a strong habit to eat snacks (2d) hinders the mediation of plan enactment. Methods This study was a self-reported longitudinal online survey study. A total of 428 participants filled in a survey, measuring demographic factors (e.g. gender, age, education level), several socio-cognitive constructs (i.e. attitudes, self-efficacy, habit, action planning, plan enactment), and fruit consumption, at three points in time (baseline, after 1 month, and after 3 months). Mediation and moderated mediation analyses were used to investigate the planning-plan enactment- fruit consumption relationship. Results Up to 70% of the participants reported to have enacted their T1 action plans at T2. Action planning on fruit consumption was fully mediated by plan enactment (Hypothesis 1). All four proposed moderators (i.e. intention, self-efficacy, habit to consume fruit, and habit to consume snacks) significantly influenced the mediation (Hypotheses 2a-2d). Mediation of plan enactment was only present with high levels of intention, high levels of self-efficacy, strong habits to eat fruit, and weak habits to eat snacks. Conclusion The study suggests the importance of plan enactment for fruit consumption. Furthermore, it emphasizes the necessity of facilitating factors. High levels of intention, self-efficacy and a strong habit to consume fruit clearly aid the enactment of action plans. This suggests that when these factors are moderately low, plan enactment may fail and thus an intervention may require first steps to foster these moderating factors.